Craniocervical posture: cephalometric and biophotogrammetric analysis - Priscila Weber; Eliane Castilhos Rodrigues Corrêa; Jovana M. Milanesi; Juliana Corrêa Soares; Maria Elaine Trevisan (Universidade Estadual de Campinas, 2015)
Aim: To investigate the correlation between the craniocervical posture measurements obtained by the biophotogrammetric and cephalometric analysis. Methods: 80 women aged between 19 and 35 years were evaluated by the cephalometric and biophotogrammetric methods. The cephalometric variables were: CVA (position of flexion/extension of the head) CPL (forward head posture) CVT/EVT ratio (cervical column curvature). For the biophotogrammetric analysis, photography were analyzed in right profile being two angles related to the head forward posture (A1 and A2) and one related to flexion-extension head position (FE). It was also measured the curvature of the cervical spine by the cervical distance. The correlation between the craniocervical posture variables, as measured by the two methods of assessment, was analyzed by the Pearson's correlation with a significance level of 5%. Results: It was observed a moderate and significant agreement (p=0.00) between the postural craniocervical variables that analyzed the flexionextension head position (FE and CVA) and the forward head (CPL and A1). The evaluation of the cervical curvature by the DC measure showed no correlation with the cephalometric variable CVT/EVT. Conclusions: The biophotogrammetric analysis can be preferably chosen for assessing the head posture. However, the cephalometric analysis appears to be the most indicated for the cervical curvature measurement, since it enables a more objective view of the bone structures without the influence of the soft tissues.